Manual External Skeletal Distraction of Restricting Soft Tissue after Release of Long-Standing Burn Contractures - Swain, Bharatendu; Shravya, C.; Sampreethi, Shalini (Indian Journal of Plastic Surgery, 2025)
Long-standing burn contractures of limb joints are resistant to complete surgical release and have been addressed earlier by serial casting, and more recently, distraction with a distractor, mostly limited to small joints of the hand. This retrospective study of patients with long-standing burn contracture was done to evaluate the efficacy of external skeletal distractors in securing complete release of various affected joints.In our series, complete release was achieved through gradual manual distraction using skeletal uni- and multiplanar frameworks across the affected limbs after incisional release. The resultant wound after complete release was skin grafted or covered with flaps.Thirty-one limbs in 27 young patients (average age: 19 years) with long-standing contractures (18.5 years) due to burns underwent manual soft tissue distraction in order to achieve complete release (50–95 degrees across various joints). All patients achieved complete release of contractures with minimal complications.Gradual manual soft tissue distraction through external skeletal distractors of restricting soft tissue (“stretch as you go”) after incisional release in long-standing burn contracture of limb joints achieves complete release without exposure of vital structures.
Keywords: postburn contracture; external fixators; soft tissue distraction; manual distraction; joint forces.